Leaf area index, plant density and water management of coffee - Rezende, Fátima Conceição; Dias Caldas, André Luiz; Scalco, Myriane Stella; Faria, Manoel Alves de (Coffee Science - ISSN 1984-3909, 2014)
Water stress can affect the canopy architecture, the use of radiation and reduce leaf area index. The leaf area index is a parameter that is a directly related to evapotanspiration. Was evaluated the leaf area index of coffee in a function of tillage system and irrigation management in a orchard of coffee, cv. Rubi MG-1192, drip irrigation. A randomized block experimental design with split-plot (density in plots and subplot irrigation treatments) and four replications. Was adopted three irrigation management: no irrigation (T0), irrigated when t soil water tension reached 60 kPa in tensiometers installed at 0.25 m depth (T2) and irrigated Monday, Wednesday and Friday, replacing the depth evapotranspiration (T3), under four planting densities (2500, 3333, 5000 and 10000 plants ha-1). Leaf area index was measured from April to December of 2009 and 2010 and April to September of 2011 the late afternoon using the Canopy Plant Analyzer (LAI 2000). Measurements were taken in a plot with 10 plants and the data represent the average of the readings. The leaf area index tends to increase with the increase of planting density and varies throughout the year, suffering strong influence of harvest and occurrence of diseases and pest. Irrigation can providing greater leaf area index independent of plant density and tends to present higher effect on density of 2500 plants ha-1.